Intergroup Biases in Fear-induced Aggression - Mifune, Nobuhiro; Simunovic, Dora; Yamagishi, Toshio (Frontiers in Psychology, 2017)
Using a recently created preemptive strike game (PSG) with 176 participants, we investigated if the motivations of spite and/or fear promotes aggression that requires a small cost to the aggressor and imposes a larger cost on the opponent, and confirmed the earlier finding that fear does but spite does not promote intergroup aggression when the groups are characterized as minimal groups; additionally, the rate of intergroup aggression did not vary according to the group membership of the opponent. The PSG represents a situation in which both the motivations of spite and of fear can logically drive players to choose an option of aggression against an opponent. Participants decide whether or not to attack another participant, who also has the same capability. The decision is made in real time, using a computer. We discuss theoretical implications of our findings on the evolutionary foundations of intragroup cooperation and intergroup aggression. The evolutionary model of intergroup aggression, or the parochial altruism model, posits that intragroup cooperation and intergroup aggression have co-evolved, and thus it predicts both intragroup cooperation and intergroup aggression to emerge even in a minimal group devoid of a history of intergroup relationships. The finding that only intragroup cooperation but not intergroup aggression emerged in the minimal group experiments strongly suggests that intergroup aggression involves a psychological mechanism that is independent from that of intragroup cooperation. We further discuss the implications of these findings on real-world politics and military strategy.